Determinants of Mobile Phone Penetration: Panel Threshold Evidence from Sub-Saharan Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
Despite the evolving literature on the development benefits of mobile phones, we still know very little about factors that influence their adoption. Using twenty five policy variables, we investigate determinants of mobile phone penetration in 49 Sub-Saharan African countries with data for the period 2000-2012. The empirical evidence is based on contemporary and non-contemporary OLS, Fixed effects, System GMM and Quantile regression techniques. The determinants are classified into six policy categories. They are: (i) macroeconomic, (ii) business/bank, (iii) market-related, (iv) knowledge economy, (v) external flows and (vi) human development. Results are presented in terms of threshold and non-threshold effects. The former has three main implications. First, there are increasing positive benefits in regulation quality, human development, foreign investment, education, urban population density and internet penetration. Second, there is evidence of decreasing positive effects from patent applications. Third, increasing negative impacts are established for foreign aid and return on equity. Non-threshold tendencies are discussed. Policy implications are also covered with emphasis on policy syndromes to enhance more targeted implications for worst performing nations.
Keywords: C23; L96; O11; O33; O55; 330; Panel data; Mobile phones; Development; Africa